DYSFUNCTION OF THE BLADDER - V. V. Borisov (Вестник урологии, 2014)
The lecture presents a modern view of the anatomical and functional properties of the bladder on the mechanisms leading to its dysfunction. The study is based on an analysis of the national literature of recent decades.